Genetic analysis of calf survivability in crossbred cattle - Pathak, Kanai; Koloi, Subrata; Ghosh, Monoj K.; Karunakaran, M; Mandal, Ajoy (Indian Journal of Dairy Science, 2018)
Data on survivability traits of Jersey crossbred calves, maintained at the cattle yard of the Eastern Regional Station of ICAR-NDRI, Kalyani, over last 35 years (1982-2016) were collected to study the effect of genetic and non-genetic factors on survivability traits of calf and their genetic control. Least squares analysis of variance with fitting constant was applied to determine the effect of genetic and non-genetic sources of variations on different survivability traits (survivability from birth to -3, -15, -30, -90, -180 and -365 days) of calves. The overall mortality (%) of crossbred calves up to 1 year of age in the herd was 28.90%. In the present study, the least squares means of survivability percent upto -3 days, -15 days, -30 days, -90 days, -180 days and -365 days were 94.80±0.68, 89.40±1.41, 84.88±1.56, 76.60±2.50, 74.66±3.25 and 71.27±3.22, percent respectively. The study showed that random effects of sire had significant effect on calf survivability percent upto day -90, -180 and -365. Genetic groups of calves had non-significant influences on all survivability traits considered for this study. Period of birth had significant effect on all the traits except day 0-3. Season of birth had significant effect on survivability upto -3, -180, -365 & -365 days. Parity of dam had no significant effect on any of the traits. Sex of the calf had significant effect on all the traits except day 0-365. Birth weight of calves had significant effect on all the traits (P < 0.01). The heritabilities of calf survivability at different ages were low in magnitude, ranging from of 0.01 to 0.12.Genetic and phenotypic correlations among all the survivability traits at different ages were moderate to high, ranging from 0.16-1.00 in this study.